2015
DOI: 10.1590/s1517-707620150003.0078
|View full text |Cite
|
Sign up to set email alerts
|

Production of porous ceramic materialusing different sources of alumina and calcia

Abstract: Numerous papers and publications report the use of microporous calcium hexaluminate (CaO.6Al 2 O 3 ; CA 6 ) as a key raw material for high temperature insulating materials. This material has unique properties with respect to chemical purity and mineral composition. Another important property of CA 6 is its structure, which consists of platelet-shaped crystals that interlock. The free distance between the crystals defines the microporous structure. The low density in combination with the micropores hampers heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
1
0
2
Order By: Relevance
“…As the sintering temperature increases, the bulk density increases, and the porosity decreases (5.4 and 3.0 % respectively); this fact explains why the volumetric shrinkage value shown in Table 2 is higher for the material sintered at 1500°C. In another work [28], a porous ceramic material was processed from commercial Al 2 O 3 and commercial CaCO 3 by mechanical milling, uniaxial compaction, and sintering. The authors reported an apparent poro- sity of more than 20 %, with an average pore size of 1 µm, while the apparent porosity in the materials of the present work, sintered at 1450°C and 1500°C is 5.4 and 3.0 % respectively, with pore sizes between 0.5 and 20 micrometers.…”
Section: Density and Mechanical Propertiesmentioning
confidence: 99%
“…As the sintering temperature increases, the bulk density increases, and the porosity decreases (5.4 and 3.0 % respectively); this fact explains why the volumetric shrinkage value shown in Table 2 is higher for the material sintered at 1500°C. In another work [28], a porous ceramic material was processed from commercial Al 2 O 3 and commercial CaCO 3 by mechanical milling, uniaxial compaction, and sintering. The authors reported an apparent poro- sity of more than 20 %, with an average pore size of 1 µm, while the apparent porosity in the materials of the present work, sintered at 1450°C and 1500°C is 5.4 and 3.0 % respectively, with pore sizes between 0.5 and 20 micrometers.…”
Section: Density and Mechanical Propertiesmentioning
confidence: 99%
“…The porous structures produced typically show a small average pore size and higher strength, which are features particularly attractive in the production of thermal insulators [14,27]. The process requires a careful preparation of stable low-viscosity codispersions of particles of Al 2 O 3 and CaO sources [28,29], the definition of an adequate heating schedule for the drying, dehydroxylation, and decarbonation steps [6,14], and use of hydraulic binders prior to sintering. However, little attention has been devoted to the role of such binders in the evolution of the physical properties of porous CA 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Apesar disso, eles abrem a possibilidade para sua utilização como um material poroso para temperaturas elevadas, como no caso dos isolamentos térmicos, onde a resistência à densificação e a preservação dos altos níveis de porosidade a alta temperatura são mais importantes do que a resistência mecânica [18,19]. Nestas aplicações, a heterogeneidade do grão e a expansão volumétrica resultante das reações in situ conferem uma resistência intrínseca à densificação que ajuda a preservar os poros até altas temperaturas e por períodos prolongados [20].…”
Section: Al 3+unclassified
“…Eles serão comparados com as amostras de referência AF-Mold, AF-Pren [18], AG-Mold e AG-Pren. [18,19,23,[89][90][91][92][93] e, portanto, modificar as propriedades mecânicas.…”
Section: Amostras Produzidas a Partir De Hexaluminato De Cálcio Pré-funclassified